FILOSOFI UPACARA MELASTI SERANGKAIAN HARI SUCI NYEPI TAHUN BARU SAKA 1945 BAGI UMAT HINDU KALIMANTAN TENGAH - Ni Wayan Gateri; I KETUT SUBAGIASTA (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
An article entitled The Philosophy of the Melasti Ceremony as a Series of Nyepi Holy Days for the Saka New Year 1945 for Hindus in Central Kalimantan. Philosophically, the Melasti Ceremony means a spiritual and physical purification ceremony for the impurities that occur in the universe according to the teachings of Hinduism. The essence of the description of this article is about the time of the Melasti Ceremony, its literary sources, the place of the Melasti Ceremony, Nyasa or the Melasti Ceremony Symbol, the Purpose of the Melasti Ceremony, the Manggala Melasti Ceremony, the Offerings, the Religious Facilities for the Melasti Ceremony, the Meaning of the Melasti Ceremony according to the sacred literature of the Bhagavadgita, the Meaning of Melasti according to the holy book Saraamuscaya, the meaning of Melasti according to the holy book Manawadharmasastra, and the philosophy of the holy day of Nyepi for the Saka New Year 1945. The place for holding the Melasti ceremony for Hindus in Palangka Raya City, Central Kalimantan province is located on the Kahayan river, because every year the place for the Melasti ceremony has been determined on the banks of the Kahayan river near the Sukarno monument, Palangka Raya City.